2022
DOI: 10.3389/fvets.2022.841231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Capsaicin on Growth Performance, Meat Quality, Digestive Enzyme Activities, Intestinal Morphology, and Organ Indexes of Broilers

Abstract: This experiment was conducted to investigate the effects of capsaicin (CAP) on growth performance, meat quality, digestive enzyme activities, intestinal morphology, and organ indexes of broilers. A total of 256 one-day-old Arbor Acre male broilers were randomly allocated into four treatments with eight replicates of eight birds, feeding a basal diet (control group), a basal diet supplemented with 2, 4, and 6 mg/kg CAP for 42 d, respectively. The growth performance, digestive enzyme activities of intestinal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…This contrasts the effects found in Arbor Acre male broilers where the addition of 80 mg/kg pure natural capsaicin extract increased both averaged daily weight gain and final body weight in both the starter (d 1-21) and grower (d 22-42) periods, 16 and both 2 and 4 mg/kg decreased the FCR in the entire growth period (d 1-42). 14 Dietary inclusion of 10, 15, and 150 mg PheCap/kg feed resulted in lower mortality rates. Due to these lower mortality rates, EPEF of the 10 and 15 mg PheCap/kg feed treatment groups was significantly higher than the control group, with the highest numerical value in the 15 mg/kg feed group.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…This contrasts the effects found in Arbor Acre male broilers where the addition of 80 mg/kg pure natural capsaicin extract increased both averaged daily weight gain and final body weight in both the starter (d 1-21) and grower (d 22-42) periods, 16 and both 2 and 4 mg/kg decreased the FCR in the entire growth period (d 1-42). 14 Dietary inclusion of 10, 15, and 150 mg PheCap/kg feed resulted in lower mortality rates. Due to these lower mortality rates, EPEF of the 10 and 15 mg PheCap/kg feed treatment groups was significantly higher than the control group, with the highest numerical value in the 15 mg/kg feed group.…”
Section: Discussionmentioning
confidence: 97%
“…This contrasts the effects found in Arbor Acre male broilers where the addition of 80 mg/kg pure natural capsaicin extract increased both averaged daily weight gain and final body weight in both the starter (d 1–21) and grower (d 22–42) periods, 16 and both 2 and 4 mg/kg decreased the FCR in the entire growth period (d 1–42). 14…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spleen, thymus, and liver are the most important immune organs in mammals, and the quality of animal immune organs is increased by their proliferation caused by cell growth and division. Therefore, the weight is proportional to the immune function of the body ( 19 , 20 ). In this study, it was found that the organ index of mice after gavage of different doses of DBD was not significantly different from that of the control group, but the 0.5 g/ml and 2 g/ml dose groups were superior to the control group.…”
Section: Discussionmentioning
confidence: 99%